Working Together for Good Governance: The Role of NGOs in Corruption Prevention in the Cambodian Public Sector - Som, Borann (Curtin University, 2017)
The aim of this research is to explore how NGOs can become more effective in combating public sector corruption in Cambodia. In doing so, this study adopted a phenomenological approach of inquiry. As a result, it contributes to theory through the development of two different but interrelated conceptual frameworks. Also, it informs policy and practice by providing a conceptual roadmap for designing strategic directions and action for enhancing resistance to corruption in public sector organization.